2020
DOI: 10.1007/s11340-020-00615-3
|View full text |Cite
|
Sign up to set email alerts
|

Reflected Near-field Blast Pressure Measurements Using High Speed Video

Abstract: Background: The design and analysis of protective systems requires a detailed understanding of, and the ability to accurately predict, the distribution of pressure loads acting on an obstacle following an explosive detonation. In particular, there is a pressing need for accurate characterisation of blast loads in the region very close to a detonation, where even small improvised devices can produce serious structural or material damage. Objective: Accurate experimental measurement of these near-field blast eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 36 publications
(47 reference statements)
1
25
0
Order By: Relevance
“…It has been suggested that Z~0.5 m/kg 1/3 marks the transition between 'relatively consistent [loading]' in the extreme near-field and 'large variations in loading' in the late near-field (Tyas, 2019). The results in Figure 6 (Z = 0.481 m/kg 1/3 ) lend evidence to this claim; it appears as though a turbulent fireball plume -likely caused by the emergence and growth of Rayleigh- Taylor (Lord Rayleigh, 1882;Taylor, 1950) and Richtmyer-Meshkov (Meshkov, 1969;Richtmyer, 1960) surface instabilities (Rigby et al, 2020) -has impacted the central bar in Test 4 and not in Test 5. Whilst the central bar loading in Test 5 appears to be commensurate with the other radial ordinates, the central bar loading in Test 4 demonstrates an earlier arrival time, higher magnitude peak pressure and generally higher pressure-time history thereafter.…”
Section: Spherical Testsmentioning
confidence: 84%
See 1 more Smart Citation
“…It has been suggested that Z~0.5 m/kg 1/3 marks the transition between 'relatively consistent [loading]' in the extreme near-field and 'large variations in loading' in the late near-field (Tyas, 2019). The results in Figure 6 (Z = 0.481 m/kg 1/3 ) lend evidence to this claim; it appears as though a turbulent fireball plume -likely caused by the emergence and growth of Rayleigh- Taylor (Lord Rayleigh, 1882;Taylor, 1950) and Richtmyer-Meshkov (Meshkov, 1969;Richtmyer, 1960) surface instabilities (Rigby et al, 2020) -has impacted the central bar in Test 4 and not in Test 5. Whilst the central bar loading in Test 5 appears to be commensurate with the other radial ordinates, the central bar loading in Test 4 demonstrates an earlier arrival time, higher magnitude peak pressure and generally higher pressure-time history thereafter.…”
Section: Spherical Testsmentioning
confidence: 84%
“…Near-field tests were performed using the Characterisation of Blast Loading (CoBL) apparatus (Clarke et al, 2015), shown in Figure 3; originally designed to measure the output from buried explosives but since used to quantify near-field reflected blast pressures from free-air explosions (Rigby et al, 2015b(Rigby et al, , 2019b(Rigby et al, , 2020Tyas et al, 2016). The apparatus, as utlisied for this study, comprises an array of 17 Hopkinson (1914) pressure bars 152 (HPBs), suspended vertically such that their faces lie flush with the surface of a 100 mm thick, 1400 mm diameter high-strength steel plate that acts as a nominally rigid reflecting surface, under which the explosives are detonated.…”
Section: Near-field Apparatus and Data Acquisitionmentioning
confidence: 99%
“…Firstly, the high magnitude of loading necessitates the use of robust support structures and protective housing for sensitive equipment (which itself is required to record in the MHz frequency range). Secondly, the measurements themselves are highly variable owing to the presence of surface instabilities in the early stages of expansion of the detonation products (Rigby et al, 2020). It is therefore not practical to develop a predictive approach based solely on physical testing, however experimental data remains a fundamental requirement for validation of numerical modelling schemes.…”
Section: Introduction and Contextmentioning
confidence: 99%
“…Furthermore, the sudden increase in pressure at the vicinity of a detonation will cause an increase in temperature (few thousand kelvins). Finally, the transfer of momentum between the shock front and solid particles will also cause these solid particles to accelerate spherically away from the center [23][24][25]. The combined effect will result in the creation of an optically thick visible fireball.…”
Section: Introductionmentioning
confidence: 99%